2016
DOI: 10.1007/s11060-016-2190-1
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab: first experience with recurrent primary central nervous system (CNS) tumors

Abstract: Patients with progressive primary brain tumors (PBT) are attracted to promising new treatments, even prior to convincing data. Anti-PD1 immunotherapies have been in the spotlight since publication of groundbreaking results for metastatic melanoma with pembrolizumab (PBL). Our objective was to report on the response and toxicity of PBL in patients with advanced PBT. We retrospectively reviewed the charts of 22 patients (17 adults and 5 children) with recurrent central nervous system tumors treated with PBL. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 43 publications
1
52
2
1
Order By: Relevance
“…On the other hand, there are also conflicting results. A recently published retrospective analysis of 22 patients with heavily pretreated refractory progressive primary brain tumors (including 10 with GBM) treated with pembrolizumab as a salvage agent in four major Israeli brain tumor centers showed only limited OS of no more than 3.2 months (139). The authors do not recommend further use of pembrolizumab for the recurrent primary brain tumors until convincing positive prospective clinical trial data is published.…”
Section: The Role Of Immune Checkpoint Inhibitors In Glioblastoma Immmentioning
confidence: 99%
“…On the other hand, there are also conflicting results. A recently published retrospective analysis of 22 patients with heavily pretreated refractory progressive primary brain tumors (including 10 with GBM) treated with pembrolizumab as a salvage agent in four major Israeli brain tumor centers showed only limited OS of no more than 3.2 months (139). The authors do not recommend further use of pembrolizumab for the recurrent primary brain tumors until convincing positive prospective clinical trial data is published.…”
Section: The Role Of Immune Checkpoint Inhibitors In Glioblastoma Immmentioning
confidence: 99%
“…Blumenthal et al reported their experience of pembrolizumab in patients with recurrent brain tumors including 5 pediatric patients, but they failed to show a benefit on overall survival [39]. The obvious exceptions are pediatric patients with refractory Hodgkin lymphoma (HL) which have shown durable responses to pembrolizumab [40,41].…”
Section: Immune Checkpoint Inhibitors and Clinical Trialsmentioning
confidence: 99%
“…Although clinical trials have shown tumor responses in some patients, few are major responses and most have not been durable [12,3941]. There is a need to better understand the mechanisms of action of PD-1/PD-L1 in these pediatric tumors, to determine if there is an underlying genetic resistance to ICIs [13,96].…”
Section: Limitations Of Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Pembrolizumab has proven safe and efficacious in the treatment of a host of diseases, including NSCLC [26][27][28][29], melanoma [26,30], malignant mesothelioma [31], Hodgkin lymphoma [32][33][34], urothelial cancer [35,36], breast cancer [37], and progressive primary brain tumors [38]. Pembrolizumab has rarely been utilized in the gynecologic setting; however, it has been reported to have a favorable safety profile and durable antitumor activity in cervical and endometrial cancer [39][40][41] as well as gestational trophoblastic neoplasia [42].…”
Section: Discussionmentioning
confidence: 99%